Gruppenaufnahme
Ministerpräsident Saarland Werner Zeyer; Ministerpräsident Baden-Württemberg Lothar Späth; Ministerpräsident Rheinland-Pfalz Bernhard Vogel; Präsident Deutscher Bundestag Richard Stücklen; Ministerpräsident Bayern Franz Josef Strauß; Ministerpräsident Niedersachsen Ernst Albrecht;